Natural history of the West Indies - Fernández de Oviedo y Valdés, Gonzalo, 1478-1557 (Department of Romance Studies at the University of North Carolina, 2018)
Where the only previous translations of Gonzalo Fernandez de Oviedo's Natural History of the West Indies (1555 and 1625) are now unreadable, Sterling A. Stoudemire's translated edition offers this foundational text to the modern reader in an accessible format. The original text, published in 1525, is a beautiful Gothic example of the early Spanish-American chronicle, and is of great rarity. It offers the eyewitness account of a true historian and naturalist, and is the source of some of Europe's first descriptions of the flora and fauna of the Americas. Stoudemire offers comprehensive introductory material on the author of the text and its writing, drawing not only on the original text, but the excellent work of Enrique Alvarez Lopez, a naturalist who has published excellent versions of the Natural History in modern Spanish. This leads Stoudemire's English version to be a beautiful rendition that is both accurate and readable. It presents the heart of Oviedo's work without the interminable unpunctuated sentences of the original, and as such is an excellent introduction to both the Chronicle as a genre, and to Oviedo's oeuvre.
Keywords: America -- Early accounts to 1600.; Indians of the West Indies.; Indians of Central America.; Natural history -- West Indies.; Natural history -- Central America.; Amérique -- Récits avant 1600.; Peuples autochtones -- Antilles.; Peuples autochtones -- Amérique centrale.; Sciences naturelles -- Antilles.; Sciences naturelles -- Amérique centrale.; HISTORY -- United States -- State & Local -- General.; HISTORY -- Expeditions & Discoveries.; Indians of Central America; Indians of the West Indies; Natural history; America; Central America; West Indies; Early works